2012
DOI: 10.1074/jbc.m112.357061
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Investigation on the Binding Specificity of Sialyldisaccharides with Hemagglutinins of Influenza A Virus by Molecular Dynamics Simulations

Abstract: Background: Recognition of terminal sialyldisaccharides by influenza A hemagglutinin initiates the infection process of influenza. Results: MD simulations on sialyldisaccharide-hemagglutinin (H1, H3, H5, and H9) complexes reveal the molecular basis of specific recognition. Conclusion:The order of the binding specificity of Neu5Ac␣(2-3)Gal and Neu5Ac␣(2-6)Gal is H3 Ͼ H5 Ͼ H9 Ͼ H1 and H1 Ͼ H3 Ͼ H5 Ͼ H9, respectively. Significance: The insights from this study will help in designing carbohydrate-based therapeutic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 55 publications
0
19
0
Order By: Relevance
“…For the simulations, the force field ff99 of AMBER12 (Assisted Model Building with Energy Refinement) is used for protein and GAFF (General Amber Force Field) for saccharide (Wang et al, 2000;Wang et al, 2004;Case et al, 2012). GAFF force field for carbohydrates produces reliable results when used alongside ff99 for proteins (Veluraja and Margulis, 2005;Yan et al, 2008;Priyadarzini et al, 2012;Parasuraman et al, 2014). Necessary sodium ions are added to neutralize the galectin-glycan complexes.…”
Section: Molecular Dynamics Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the simulations, the force field ff99 of AMBER12 (Assisted Model Building with Energy Refinement) is used for protein and GAFF (General Amber Force Field) for saccharide (Wang et al, 2000;Wang et al, 2004;Case et al, 2012). GAFF force field for carbohydrates produces reliable results when used alongside ff99 for proteins (Veluraja and Margulis, 2005;Yan et al, 2008;Priyadarzini et al, 2012;Parasuraman et al, 2014). Necessary sodium ions are added to neutralize the galectin-glycan complexes.…”
Section: Molecular Dynamics Simulationsmentioning
confidence: 99%
“…Molecular dynamics (MD) simulation studies are widely used in studying the conformational analysis of carbohydrates, proteincarbohydrate interactions, and the dynamical behavior of the complexes (Karplus and McCammon, 2002;Fadda and Woods, 2010;Veluraja et al, 2010;Priyadarzini et al, 2012;Selvin et al, 2012;Venkateshwari and Veluraja, 2012). Modeling of carbohydrates into the binding pocket of proteins and the carbohydrate mediated recognition processes have been reported earlier because of its crucial role in studying the protein-carbohydrate interactions (Weis and Drickamer, 1996;Agostino et al, 2012;Priyadarzini et al, 2012;Sarkar and Pérez, 2012). Hydrogen bonds, hydrophobic contacts, electrostatic interactions, van der Waals, and π-stacking interactions play a major role in the molecular recognition processes of protein-carbohydrate interactions (Hunter and Sanders, 1990;Weis and Drickamer, 1996;Mannhold et al, 2006;Wheeler et al, 2010;Sarkar and Pérez, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Terminal SAs of cell membrane glycoprotein, the natural receptor for HA-mediated viral adsorption, sit on top of two aromatic residues of HA1 (Y98 and W153 at the bottom of the binding pocket) [14]. Accordingly, a theoretical investigation by molecular dynamics (MD) simulation revealed that Y91 at the bottom of binding pocket of HA1 forms hydrogen bonds with α-2,3 or α-2,6 linked terminal SAs in various HA subtypes [15]. Besides, the binding sites in the pocket are of conserved amino acids that is edged by 190-helix at the top of the pocket, and the 130- and 220-loops located at the front edge and the left side of the pocket, respectively [9].…”
Section: Antivirals Targeting Ha1mentioning
confidence: 99%
“…In other words, to acquire its infectivity in human, avian influenza viruses have to acquire adequate binding avidity to α-2,6 linked terminal SAs through accumulated genetic drift and/or reassortments. A theoretical investigation by MD simulation [15] found that residues in 130-loop (R130, V132, T133, A134, S142), 190-helix (D187) and 220-loop (G222, Q223, A224) of H1-typed HA1 form direct or water-mediated hydrogen bonds with α-2,3 linked terminal SAs. However, to bind H1-typed HA1 with α-2,6 linked terminal SAs, H180 instead of D187 in 190‑helix, G225 instead of G222 in 220-loop of form direct or water-mediated hydrogen bonds.…”
Section: Antivirals Targeting Ha1mentioning
confidence: 99%
“…Molecular dynamics simulations have allowed the understanding of many biological processes, which are dynamic rather than static mechanisms. Regarding influenza, molecular dynamics simulations have been applied extensively to study the molecular basis of HA binding preference [10][12], as well as mutations that affect binding preference [13], [14].…”
Section: Introductionmentioning
confidence: 99%